Invasion debt – quantifying future biological invasions. Issue 4 (20th December 2015) - Rouget, Mathieu; Robertson, Mark P.; Wilson, John R. U.; Hui, Cang; Essl, Franz; Renteria, Jorge L.; Richardson, David M.
Abstract: Aim: We develop a framework for quantifying invasions based on lagged trends in invasions ('invasion debt') with the aim of identifying appropriate metrics to quantify delayed responses at different invasion stages – from introduction to when environmental impacts occur. Location: World‐wide; detailed case study in South Africa. Methods: We define four components of invasion debt: the number of species not yet introduced but likely to be introduced in the future given current levels of introduction/propagule pressure; the establishment of introduced species; the potential increase in area invaded by established species (including invasive species); and the potential increase in impacts. We demonstrate the approach in terms of number of species for 21 known invasive Australian Acacia species globally and estimate three components of invasion debt for 58 Acacia species already introduced to South Africa by quantifying key invasion factors (environmental suitability, species invasion status, residence time, propagule pressure, spread rate and impacts). Results: Current global patterns of invasive species richness reflect historical trends of introduction – most acacia species that will become invasive in southern Africa have already invaded, but there is a substantial establishment debt in South and North America. In South Africa, the likely consequence of invasion debt over the next 20 years was estimated at: four additional species becoming invasive with an average increase of 1075 km 2 invaded area per invasive species. We estimate that this would require over US 500 million to clear. Main conclusions: Our results indicate that invasion debt is a valuable metric for reporting on the threats attributable to biological invasions, that invasion debt must be factored into strategic plans for managing global change, and, as with other studies, they highlight the value of proactive management. Given the uncertainty associated with biological invasions, further work is required to quantify the different components of invasion debt.